Effect of Storage Moulds on the Nutritional Quality of Kolanuts in Nigeria - Agbeniyi, S.O.; Ayodele, M.S. (Pakistan Journal of Nutrition, 2010)
Proximate analysis of healthy and infested kolanuts (Cola nitida and C. acuminata) was carried out at the Cocoa Research Institute of Nigeria, Ibadan, Nigeria, to determine the effect of mould attack on the nutritive value of stored kolanuts. The storage moulds encountered on both species of kolanuts in Nigeria were Lasiodiplodia theobromae, Fusarium pallidoroseum, F. moniliforme, F. cavispermum, Aspergillus niger, A. fumigatus, A. flavus, and Paecilomyces variotii. Proximate analysis of healthy and infested C. nitida revealed 0.79% and 1.29% soluble sugar in healthy and infected kolanuts respectively. The healthy Cola acuminata has 54% moisture content compared to 23.24% in the infested nuts. The percentage of crude protein in healthy nuts was 4.55% but it was 2.1% in the infested nuts. Macro elements of the kolanuts indicated significant differences in calcium, potassium, magnesium and phosphorus between healthy and infested nuts. There was an increase in caffeine content of diseased C. nitida and a significant decrease (p=0.05) in percentage protein and moisture content in such infested kolanuts. The activities of the isolated mould are implicated in the deterioration of these biochemical substances in kolanuts.